Quality of Life of Rag Pickers in Mysuru City: A Case Study - Girisha (International Journal of Rural and Regional Development, 2025)
The purpose of this research paper is to examine the socio-economic conditions and quality of life of rag pickers in Mysuru City. Informal waste management is significantly impacted by rag pickers, who are among the most marginalized urban populations. Despite their important contributions, they are subjected to poor living conditions, a lack of social security, and significant health risks. This study employs both qualitative methods to analyze the challenges faced by rag pickers and proposes policy recommendations, including health interventions, social work initiatives, and policy reforms, to enhance their overall quality of life and ensure their integration into the formal economy. The study recommended the comprehensive policy measures, along with social and economic support and social work interventions are essential to uplift this vulnerable group, and integrate them into the formal economy. The rag pickers not only their living conditions can be improved there is holistic approach requires to stabilize their the living conditions.
Keywords: Quality of life; Rag pickers; informal waste management; socio-economic conditions